2018
DOI: 10.15381/rpb.v25i2.14289
|View full text |Cite
|
Sign up to set email alerts
|

Composición química del aceite esencial de las hojas de Hedyosmum luteynii Todzia (Chloranthaceae)

Abstract: El objetivo de este trabajo fue la caracterización química del aceite esencial de Hedyosmum luteynii, a partir de muestras recolectadas en el bosque natural Jacarón, cantón Colta, provincia de Chimborazo, Ecuador. El aceite esencial se extrajo por hidrodestilación; el análisis de la composicion se realizó mediante un cromatógrafo de gases acoplado a un espectrómetro de masas; la identificación de los componentes se realizó por comparación de sus espectros de masas y de los índices de Kováts reportados en la li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…There are no previous reports about the extraction of EO from H. strigosum , however, a study from a related species, H. luteynii , from Chimborazo-Ecuador, reported a very low yield of the EO of ca. 0.07% by using the same extraction method [ 14 ]. In contrast, by means of microwave radiation-assisted hydrodistillation from H. translucidum , the EO yield obtained was 1.2% [ 20 ], approximately twice the yield obtained in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no previous reports about the extraction of EO from H. strigosum , however, a study from a related species, H. luteynii , from Chimborazo-Ecuador, reported a very low yield of the EO of ca. 0.07% by using the same extraction method [ 14 ]. In contrast, by means of microwave radiation-assisted hydrodistillation from H. translucidum , the EO yield obtained was 1.2% [ 20 ], approximately twice the yield obtained in our study.…”
Section: Discussionmentioning
confidence: 99%
“…All the reported species for Ecuador grown mainly in cloud forests between 600 and 3000 m a.s.l. [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoterpenes were the main components of the EO that was hydrodistilled from fresh leaves; α-phellandrene (32.72%), α-pinene (13.20%), (Z)-β-ocimene (10.99%), silvestrene (6.51%), bicyclogermacrene (5.05%), 1,8-cineol (4.95%), (E)-β-ocimene (3.88%), and germacrene D (3.20%) predominated [47].…”
Section: Hedyosmum Luteynii Todziamentioning
confidence: 99%
“…Similarly, the EO H. racemosum presents sabinene and β-pinene, which are common compounds in the EO of Hedyosmum species. Torres et al [ 14 ] in 2018 reported the chemical composition of EO of Hedyosmum luteynii Todzia from the main compounds; α-phellandrene (32.72%), α-pinene (13.2%), and germacrene D (3.2%) were also identified in EO H. racemosum as main compounds.…”
Section: Discussionmentioning
confidence: 99%